2006
DOI: 10.1002/jor.20285
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar body fusion with a bioresorbable cage in a goat model is delayed by the use of a carboxymethylcellulose‐stabilized collagenous rhOP‐1 device

Abstract: The purpose of this study was to evaluate the efficacy of recombinant human osteogenic protein-1 (rhOP-1) with a carboxymethylcellulose-stabilized collagenous carrier as a bone graft substitute for instrumented lumbar spinal fusion in an established goat model. Twenty goats received a resorbable poly-L-lactic acid (PLLA) interbody cage packed with either rhOP-1 and its carrier or autologous bone graft. The carrier material was bovine collagen type-1 stabilized with carboxymethylcellulose. The fusion segments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…CMC and HPMC are considered suitable carriers based on evidence that both substances support the osteoinductive capacities of BMP‐25, 21–27 and BMP‐7,6–10, 28 as well as the osteoconductive properties of bone substitutes 29. However, whether CMC or HPMC can control the formation or the activity of osteoclasts and osteoblasts is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…CMC and HPMC are considered suitable carriers based on evidence that both substances support the osteoinductive capacities of BMP‐25, 21–27 and BMP‐7,6–10, 28 as well as the osteoconductive properties of bone substitutes 29. However, whether CMC or HPMC can control the formation or the activity of osteoclasts and osteoblasts is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the successful use of goat models to study the spine 192021. Therefore, although the results cannot be directly extrapolated to humans the experimental results obtained may play an important role in guiding human lumbar anterior surgery.…”
Section: Discussionmentioning
confidence: 99%
“…80 This is likely due to the putty component of the BMP-7 preparation, which recruits multinucleated giant cells. 113 Bone morphogenetic protein-2 BMP-2 is a potent osteoinductive molecule that has been shown to increase and speed up osteogenic differentiation, and induce healing of intrabony periodontal defects as well as critical size defects in animals. 82,86,105,114 BMP-2 applied to osteoprogenitor cells 5,115,116 and/or to osteoconductive scaffolds 22,43,76,[81][82][83][84][85][86]105,114 stimulates osteogenic differentiation in vitro and accelerates bone healing and new bone formation in vivo (Table 3).…”
Section: Bone Morphogenetic Protein-7mentioning
confidence: 99%